Sutureless closure of Operative Skin Wounds - Nagpal, BM (Med J Armed Forces India, 2004)
Good tissue union and cosmetically acceptable scar is vital for ideal surgical practice. Since their discovery in 1949, cyanoacrylate compounds have evoked interest as being the ideal “tissue glue”. Several different forms of this compound have been developed in order to eliminate tissue toxicity. In this article, we have described a technique of sutureless closure of operative skin wounds and compared it to closure of skin with silk. Inter-group comparison was carried out with respect to the time required for closure, rate of infection, cosmesis and patient acceptance. N-butyl 2-cyanoacrylate was used for sutureless skin closure in 100 patients and compared with skin closure with sutures. The time taken to close the wounds with cyanoacrylate was found to be significantly less, the cosmetic outcome better and patient acceptability higher than when sutures were used.